2017
DOI: 10.1089/dna.2016.3540
|View full text |Cite
|
Sign up to set email alerts
|

miR-224 Affects Mammary Epithelial Cell Apoptosis and Triglyceride Production by DownregulatingACADMandALDH2Genes

Abstract: MicroRNAs (miRNAs) are small noncoding RNA molecules that involve in various biological functions by regulating the expressions of target genes. In recent years, many researchers have demonstrated that miR-224 played an important role in regulating lipid metabolism. Therefore, in this study, the target genes of miR-224 were verified and the regulatory role of miR-224 was confirmed in lipid metabolism. In this study, bioinformatics methods were used for primarily predicting the target gene of miR-224 and dual-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…MiR-224 was reported to inhibit cell proliferation and metastasis in NSCLC A549 cell lines. 41 Shen et al 45 reported that miR-224 could downregulate gene expression of ACADM and ALDH2, inhibit the formation of triglyceride and influence lipid metabolism and apoptosis. Therefore, it is hypothesized that the profiles of miR-23a, miR-25, miR-145 and miR-224 might be associated with the inflammation, oxidative stress, immune imbalance, EMT, cell proliferation, apoptosis and lipid metabolism of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-224 was reported to inhibit cell proliferation and metastasis in NSCLC A549 cell lines. 41 Shen et al 45 reported that miR-224 could downregulate gene expression of ACADM and ALDH2, inhibit the formation of triglyceride and influence lipid metabolism and apoptosis. Therefore, it is hypothesized that the profiles of miR-23a, miR-25, miR-145 and miR-224 might be associated with the inflammation, oxidative stress, immune imbalance, EMT, cell proliferation, apoptosis and lipid metabolism of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, U6 and GADPH are expressed at relatively constant levels in normal and pathological conditions. These genes may be used as housekeeping genes in brain damage ( Chi et al, 2014 ; Alarcon et al, 2015 ; Li G. et al, 2016 ; Shen et al, 2016 ). There are no significant differences in the expression of U6 and GADPH in the gene expression patterns in the cerebral cortex of mice infected with PHEV detected using microarray in our previous study ( Lan et al, 2014 ), so we take them as internal reference genes for the relative quantification of other genes in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The quantification of miRNAs was performed using the Bulge-Loop TM miRNA qRT-PCR Primer Set (RiboBio, China). miR-21a-5p and Caskin1 expressions were determined by RT-PCR using SYBR Green Master Mix kit as described previously ( Shen et al, 2016 ). The relative expression was analyzed using the 2 -ΔΔCT method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain miRNAs have been reported to either promote or inhibit triglyceride production and to suppressapoptosis of MECs at growing stages. For instance, miR-224 overexpression could decrease triglyceride synthesis and promote apoptosis 12 . Bta-miR-29b promotes triglyceride production and suppress apoptosis 11 .…”
Section: Introductionmentioning
confidence: 99%